2013
DOI: 10.1371/journal.pone.0057924
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Susceptibility Mapping Differentiates between Blood Depositions and Calcifications in Patients with Glioblastoma

Abstract: ObjectivesThe application of susceptibility weighted imaging (SWI) in brain tumor imaging is mainly used to assess tumor-related “susceptibility based signals” (SBS). The origin of SBS in glioblastoma is still unknown, potentially representing calcifications or blood depositions. Reliable differentiation between both entities may be important to evaluate treatment response and to identify glioblastoma with oligodendroglial components that are supposed to present calcifications. Since calcifications and blood d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
127
0
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 42 publications
9
127
0
3
Order By: Relevance
“…34 SWI can effectively demonstrate intratumoral calcification as well, 23,70,76,112,118 with hypointensity seen on SW images, which correlates with CT findings (Fig. 4).…”
Section: Detecting and Diagnosing Brain Tumorssupporting
confidence: 61%
See 2 more Smart Citations
“…34 SWI can effectively demonstrate intratumoral calcification as well, 23,70,76,112,118 with hypointensity seen on SW images, which correlates with CT findings (Fig. 4).…”
Section: Detecting and Diagnosing Brain Tumorssupporting
confidence: 61%
“…7,49 By monitoring changes in pre-and postrecanalization of the CVS, SWI can detect differences in CVS prominence before and after occlusion. 7 Thus, an equal CVS postrecanalization (that is, the appearance of similar veins in both hemispheres) is suggestive of a good clinical outcome, whereas a less prominent CVS (that is, veins in an occluded hemisphere are less prominent than veins in However, most studies 20,23,88 have focused on lesion detection in sporadic or familial cerebral cavernous malformations (CCMs), making it difficult to assess the sensitivity of SWI in detecting VMs other than CCMs.…”
Section: Monitoring Outcome In Strokementioning
confidence: 99%
See 1 more Smart Citation
“…GRE phase imaging has been reported to be useful for differentiating calcifications from hemorrhages (3,8,11). Recently, it has been suggested that QSM can enable the differentiation of diamagnetic calcifications from paramagnetic hemorrhages (9,17,18). To our knowledge, this study is the first systematic evaluation of the diagnostic accuracy of QSM and comparison between QSM and GRE phase imaging in the assessment of calcifications and hemorrhages.…”
Section: Neuroradiology: Characterization Of Intracranial Calcificatimentioning
confidence: 91%
“…Chen et al (13,15,16) and has been suggested for differentiating diamagnetic calcifications from paramagnetic hemorrhages (9,17,18). We performed this study to compare GRE phase imaging and QSM in the detection of intracranial calcifications and hemorrhages.…”
Section: Neuroradiology: Characterization Of Intracranial Calcificatimentioning
confidence: 99%